Kepentingan beberapa pasaran utama negara ASEAN kepada pembangunan industri pelancongan Malaysia - Othman, Redzuan; Mohd Salleh, Norlida Hanim (Universiti Utara Malaysia, 2007)
One noticeable feature of the Malaysian tourism industry is the dependence upon ASEAN countries for its tourist arrivals. In 1985, ASEAN countries contributed about 75% to the total tourist arrivals to Malaysia. In 2000, the figure had dropped slightly to 68% and increased back to 75% in 2004. The most important providers for tourist arrivals is dominated by Singapore, followed by Thailand and Indonesia (named as ASEAN3). The ASEAN3 controlled about 96% and 97% of the total ASEAN tourist arrivals in 2000 and 2004 respectively. Due to the importance of ASEAN3 to the growth of the Malaysian tourism industry, this study has attempted to identify and analyse economic factors influencing their arrivals to Malaysia. Among these important factors were expenses while traveling in Malaysia, their income, alternative destinations, global economic and environmental crisis, and promotional campaign for visiting Malaysia. The study empirically estimated the mentioned variables utilising the Engle-Granger cointegration framework. Findings of this study have shown that most of the coefficients estimated were statistically significant and consistent with the theoretical framework.